(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
During the past decades it has been shown that Time Dependent Density Functional Theory (TD-DFT) is able to predict accurately and efficiently the polarizability of molecules, when using appropriate exchange-correlation potentials and (large) basis sets. In recent days organic single crystals are gaining important due to good optical behaviour. The first order hyperpolarizability along with dipole moment , mean polarizability , anisotropy of the polarizability are calculated using HF/6-311++G(d, p) and B3LYP/6-311++G(d, p) basis sets for 5-fluoro-1,3-dimethyl uracil 5-1- 3FDMU.